Failure of self regulation of UK alcohol advertising. (20th January 2010) - Hastings, Gerard; Brooks, Oona; Stead, Martine; Angus, Kathryn; Anker, Thomas; Farrell, Tom
Abstract : Although the content of alcohol advertisements is restricted, Gerard Hastings and colleagues find that advertisers are still managing to appeal to young people and promote drinking